To the question of designing of estimation means for students’ professional competences - Marina A. Anisimova; Igor S. Blyaherov; Aleksandr V. Maslennikov; Aleksandr V. Morzhov (Высшее образование в России)
The article presents the methodology for designing the estimation means for students’professional competences evaluation. The methodology is based on competence approachcorresponds with the federal state educational standards (FSES). It allows to check up the level of acquired competences and relevant skills due to the FSES.